Training on Product Design and Branding for KSBI Entrepreneurs - Ovy Noviati Nuraini Magetsari; Wahyuningsih; Mona Adriana Patriyasa; Kerstan Nathanael Djaja; Arinda Deswanti Pertiwi (Mattawang: Jurnal Pengabdian Masyarakat, 2025)
This community service program addresses the issue of low visual competitiveness among MSME products, particularly those produced by members of the Komunitas Sukses Berjamaah Indonesia (KSBI), who are predominantly homemakers engaged in culinary and fashion businesses. The focus of the activity is to strengthen product design and branding capacity, enabling MSME actors to develop attractive and consistent brand identities in the era of digital marketing. The program aims to enhance participants’ knowledge and skills in understanding branding concepts, designing logos, packaging, and visual promotional content, while also fostering confidence and collaborative learning within the community. The activities were conducted using the Participatory Action Learning System (PALS) approach through participatory planning, a one-day training session, hands-on practice using Canva and Pixellab, and pre-test and post-test evaluations. The results show an average knowledge improvement of 42 points, participants successfully produced various visual designs, and a new community structure—the “KSBI Mini Creative Team”—was formed as a platform for sustaining branding assistance within the community.